Azaanthracene organic polymer as well as preparation method and application thereof

By using azathracene organic polymer as hole transport material, the problem that existing materials are difficult to have good diffusion, stability and interface compatibility at the same time is solved, and the effect of improving the stability of optoelectronic devices and photoelectric conversion efficiency is achieved.

CN119505187APending Publication Date: 2025-02-25SHENZHEN RUIXUN ORGANIC SOLAR ENERGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411405604.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

It is difficult for existing hole transport materials to have good diffusion, stability, hole selectivity, as well as low interfacial resistance and solution processability at the same time.

Method used

Azathracene organic polymer is used as hole transport material to improve molecular weight by polymerizing azathracene small molecules of phosphate, enhance stability and film formation, and form chemical bonds with the conductive oxides on the surface of the conductive glass through the formation of chemical bonds with the conductive oxides on the surface of the conductive glass to improve interface compatibility.

Benefits of technology

It significantly improves hole selectivity, reduces interface impedance, effectively suppresses non-radiative recombination, and thus improves the stability and photoelectric conversion efficiency of optoelectronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505187A_ABST
    Figure CN119505187A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of organic photoelectric materials, and particularly relates to an azaanthracene organic polymer as well as a preparation method and application thereof. The structural general formula of the azaanthracene organic polymer is as shown in # imgabs0 #, X is selected from one of O, S, N and O = S = O, i is an integer between 1 and 40, and n is an integer between 2 and 1000. The azaanthracene phosphate micromolecules are polymerized, so that the molecular weight of the azaanthracene phosphate micromolecules is increased, and the azaanthracene phosphate micromolecules have better stability, excellent film-forming property and interaction among macromolecular chains. And the value ranges of i and n ensure that the azaanthracene organic polymer has better solubility, can be dissolved in various single or mixed solvents, and has good solution processability. When the compound is applied to a photoelectric device as a hole transport material, the hole selectivity is remarkably improved, the interface impedance is reduced, non-radiative recombination is effectively inhibited, and the stability of the device is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of organic optoelectronic materials, and in particular relates to an azaanthracene organic polymer and a preparation method and application thereof. Background Art

[0002] Organic or perovskite solar cells have received extensive attention from scholars in the research field and have made rapid progress in recent years, making them one of the new photovoltaic technologies with development prospects. The excellent photoelectric conversion performance of perovskite solar cells is mainly due to the advantages of its core structure perovskite light absorption layer, such as a wide absorption spectrum, a high molar extinction coefficient, a high carrier mobility, and a small exciton binding energy.

[0003] When sunlight shines through the photoanode to the perovskite light absorption layer, the perovskite material will generate electron-hole pairs, which will undergo charge separation at the battery interface. Electrons are transferred to the positive electrode of the battery through the electron transport layer (ETL), while holes are transferred to the negative electrode of the battery through the hole transport layer (HTL). In the process of charge separation, hole transport materials (HTM) play a vital role in charge transfer and inhibiting charge recombination. Hole transport materials can be divided into three categories: polymer hole transport materials, inorganic hole transport materials, and organic small molecule hole transport materials. Among them, the solvent used to dissolve inorganic hole transport materials will dissolve and destroy the perovskite film, so this type of inorganic hole transport material can only be used in trans-structured perovskite solar cells. Compared with them, organic small molecule hole transport materials have a lot of room for improvement in terms of compactness, diffusivity, hole selectivity, interface resistance, etc. For example, the intermolecular force of phenothiazine phosphate small molecule materials is weak, and they are prone to crystallization and phase separation during the film formation process, which affects the stability of the hole transport layer. In addition, they have poor wettability, and their hole transport performance may be affected by changes in coating thickness and substrate roughness. The solubility of polymer hole transport materials in common solvents is limited, which limits their application in certain preparation processes.

[0004] Therefore, there is an urgent need to provide a hole transport material that has good diffusivity, compactness, hole selectivity, low interface resistance and solution processability. Summary of the invention

[0005] The purpose of the present application is to provide an azaanthracene organic polymer and a preparation method and application thereof, aiming to solve to a certain extent the problem that existing hole transport materials are difficult to simultaneously have good diffusivity, stability, hole selectivity, low interface resistance and solution processability.

[0006] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:

[0007] In a first aspect, the present application provides an azaanthracene organic polymer, the general structural formula of which is as follows:

[0008] Wherein, X is selected from one of O, S, N, and O=S=O, i is an integer between 1 and 40, and n is an integer between 2 and 1000.

[0009] In a second aspect, the present application provides a method for preparing an azaanthracene organic polymer, comprising the following steps:

[0010] Compound A and diethyl halogenated phosphate as raw materials, and the monomer is prepared by substitution reaction Wherein, X is selected from one of O, S, N, and O=S=O, Y1 and Y2 are independently selected from halogen, and i is an integer between 1 and 40;

[0011] The monomers are polymerized to obtain intermediate polymers Wherein, n is an integer between 2 and 1000;

[0012] The intermediate polymer is hydrolyzed to obtain an azaanthracene organic polymer.

[0013] In a third aspect, the present application provides a photoelectric device, comprising a substrate, a photoelectric functional layer, an electron transport layer, a hole transport layer and an electrode; wherein the hole transport layer contains the azaanthracene organic polymer as described above, or the azaanthracene organic polymer prepared by the above method.

[0014] The azaanthracene organic polymer provided in the first aspect of the present application improves its molecular weight by polymerizing phosphoric acid azaanthracene small molecules, so that it has better stability, excellent film-forming properties and interactions between macromolecular chains, and the interactions between its polymer chains can effectively solve the problems of poor compactness and easy diffusion of small molecules of traditional azaanthracene compounds. In azaanthracene organic polymers, the value range of i and n ensures that azaanthracene organic polymers have good solubility, can be dissolved in a variety of single or mixed solvents, and have good solution processing performance. As a hole transport material applied to optoelectronic devices, on the one hand, azaanthracene organic polymers not only have a large coverage factor and good interface compatibility for conductive substrates such as ITO and FTO, but also have good film-forming properties on the surface of conductive substrates; and the phosphate group of azaanthracene organic polymers can form chemical bonds with the conductive oxide on the surface of conductive glass, enhance the ability to bind to transparent conductive oxides, shorten the interface spacing, reduce the interface impedance, thereby enhancing the adsorption and transmission capacity of holes, and enhancing the stability of the device and other performance. On the other hand, azaanthracene organic polymers are synthesized by polymerizing phosphate azaanthracene small molecules and have good electrical conductivity, which makes it insensitive to coating thickness and the roughness of the conductive glass surface, thus showing better hole selectivity and hole transport performance. On the other hand, azaanthracene organic polymers also help to passivate the perovskite layer and inhibit the charge recombination at the interface between the perovskite active layer and the hole transport layer, which helps to improve the stability and efficiency of hole transport. In addition, azaanthracene organic polymers can better infiltrate the perovskite precursor solution, which makes it easier and more feasible to prepare the perovskite active layer over a large area. Therefore, the present application of azaanthracene organic polymers as hole transport materials is applied to optoelectronic devices, which not only significantly improves the hole selectivity, but also reduces the interface impedance, effectively inhibits non-radiative recombination, and thus improves the stability of the device.

[0015] The preparation method of the aza-anthracene organic polymer provided in the second aspect of the present application, after preparing the monomer with compound A and diethyl halogenated phosphate as raw materials, the monomer is subjected to polymerization reaction to obtain an intermediate polymer, and then subjected to hydrolysis reaction, the aza-anthracene organic polymer can be obtained. The synthesis method of the aza-anthracene organic polymer is simple and fast, and the reaction conditions are mild, which is suitable for industrial industrialization, large-scale production and application. The obtained aza-anthracene organic polymer also has good diffusivity, stability, hole selectivity, and low interfacial resistance and solution processability, and can be better applied to the hole functional layer of optoelectronic devices.

[0016] The optoelectronic device provided in the third aspect of the present application, the hole transport layer contains the above-mentioned aza-anthracene organic polymer, the aza-anthracene organic polymer not only has a large coverage factor and good interface compatibility for conductive substrates such as ITO and FTO, but also has good film-forming performance on the surface of the conductive substrate; and the phosphate group of the aza-anthracene organic polymer can form a chemical bond with the conductive oxide on the surface of the conductive glass, enhance the binding ability with the transparent conductive oxide, shorten the interface spacing, reduce the interface impedance, thereby enhancing the adsorption and transmission ability of holes, and enhancing the stability and other properties of the device. In addition, the aza-anthracene organic polymer has good conductivity, which makes it insensitive to the coating thickness and the roughness of the conductive glass surface, thus showing better hole selectivity and hole transport performance. Moreover, the aza-anthracene organic polymer can better infiltrate the perovskite precursor solution, which is conducive to the large-scale preparation of the perovskite active layer, and passivate the perovskite layer, inhibit the charge recombination at the interface between the perovskite active layer and the hole transport layer, improve the device hole selectivity, reduce the interface impedance, and improve the device stability and photoelectric conversion efficiency. It has both important scientific significance and extremely high industrial value. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0018] Figure 1 1 is a schematic flow chart of a method for preparing an azaanthracene organic polymer provided in an embodiment of the present application;

[0019] Figure 2 is a schematic structural diagram of a positive-type solar cell provided in an embodiment of the present application;

[0020] Figure 3 is a schematic structural diagram of an inverted solar cell provided in an embodiment of the present application;

[0021] Figure 4 is a schematic structural diagram of a perovskite solar cell provided in Example 2 of the present application;

[0022] Figure 5 This is a voltage-current density test diagram of a perovskite solar cell provided in Example 2 of the present application;

[0023] Figure 6 This is a voltage-current density test diagram of a perovskite solar cell provided in Example 3 of the present application;

[0024] Figure 7This is a voltage-current density test diagram of a perovskite solar cell provided in Example 4 of the present application;

[0025] Figure 8 This is a voltage-current density test diagram of the perovskite solar cell provided in Comparative Example 1 of the present application. DETAILED DESCRIPTION

[0026] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0027] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.

[0028] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can all represent: a, b, c, ab (i.e. a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0029] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0030] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "an" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0031] The weight of the relevant components mentioned in the embodiments of the present specification can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components in the embodiments of the present specification is proportionally enlarged or reduced, it is within the scope disclosed in the embodiments of the present specification. Specifically, the mass described in the embodiments of the present specification can be μg, mg, g, kg and other mass units known in the chemical industry.

[0032] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.

[0033] The term "TCO" is the abbreviation of "Transparent Conductive Oxide", which means transparent conductive oxide. It is a major category of transparent conductive films, including FTO or ITO conductive layers. TCO materials have the characteristics of wide optical band gap, high visible light transmittance, high infrared reflectivity, good conductivity, high mechanical strength, and good chemical stability, so they are widely used in the field of optoelectronics. TCO glass is a glass material coated with a transparent conductive oxide film, which is mainly used in the fields of thin-film solar cell electrodes, smart color-changing glass electrodes, heat-insulating and energy-saving windows, etc.

[0034] The term "ITO" is an abbreviation of "Indium Tin Oxide", which means indium tin oxide, a transparent conductive oxide. When it is coated on the surface of glass, ITO glass is formed. This special glass has excellent conductivity and light transmittance. It is mainly used to make liquid crystal displays, flat panel displays, plasma displays, touch screens, electronic paper, organic light-emitting diodes, solar cells, antistatic coatings, various optical coatings, etc.

[0035] The term "FTO" is the abbreviation of "F-doped Tin Oxide", which means fluorine-doped tin oxide. It is a material in which fluorine is doped in tin oxide. It is mainly used for transparent electrodes of dye-sensitized solar cells and perovskite solar cells.

[0036] In a first aspect, an embodiment of the present application provides an azaanthracene organic polymer, the general structural formula of the azaanthracene organic polymer is as follows:

[0037] Wherein, X is selected from one of O, S, N, and O=S=O, i is an integer between 1 and 40, and n is an integer between 2 and 1000.

[0038] The azaanthracene organic polymer provided in the first aspect of the embodiment of the present application improves its molecular weight by polymerizing phosphoric acid azaanthracene small molecules, so that it has better stability, excellent film-forming properties and interactions between macromolecular chains, and the interactions between its macromolecular chains can effectively solve the problems of poor compactness and easy diffusion of small molecules of traditional azaanthracene compounds. In azaanthracene organic polymers, the value range of i and n ensures that azaanthracene organic polymers have good solubility, can be dissolved in a variety of single or mixed solvents, and have good solution processing performance. As a hole transport material applied to optoelectronic devices, on the one hand, azaanthracene organic polymers not only have a large coverage factor and good interface compatibility for conductive substrates such as ITO and FTO, but also have good film-forming properties on the surface of conductive substrates; and the phosphate group of azaanthracene organic polymers can form chemical bonds with the conductive oxide on the surface of conductive glass, enhance the ability to bind to transparent conductive oxides, shorten the interface spacing, reduce the interface impedance, thereby enhancing the adsorption and transmission capacity of holes, and enhancing the stability of the device and other performance. On the other hand, azaanthracene organic polymers are synthesized by polymerizing phosphate azaanthracene small molecules and have good electrical conductivity, which makes it insensitive to coating thickness and the roughness of the conductive glass surface, thus showing better hole selectivity and hole transport performance. On the other hand, azaanthracene organic polymers also help to passivate the perovskite layer and inhibit the charge recombination at the interface between the perovskite active layer and the hole transport layer, which helps to improve the stability and efficiency of hole transport. In addition, azaanthracene organic polymers can better infiltrate the perovskite precursor solution, which makes it easier and more feasible to prepare the perovskite active layer over a large area. Therefore, the azaanthracene organic polymers of the present application are applied to optoelectronic devices as hole transport materials, which not only significantly improves the hole selectivity, but also reduces the interface impedance, effectively inhibits non-radiative recombination, and thus improves the stability of the device.

[0039] For example, in the azaanthracene organic polymers, the value of i can be 1, 2, 5, 10, 15, 20, 25, 30, 35, 40, etc., which are typical but non-limiting values ​​at any point, or any integer value between two points, and the value of n can be 2, 10, 30, 50, 80, 100, 200, 300, 500, 800, 1000, etc., which are typical but non-limiting values ​​at any point, or any integer value between two points.

[0040] In some possible implementations, the general structural formula of the azaanthracene organic polymer is as follows:

[0041]

[0042] In each structural formula, i is independently an integer between 1 and 40, and n is independently an integer between 2 and 1,000.

[0043] In some possible implementations, azaanthracene organic polymers can be easily dissolved in a variety of single or mixed solvents, such as toluene, chlorobenzene, chloroform, dichloromethane, methanol, ethanol and isopropanol, which makes them more flexible and convenient in the preparation process. By polymerizing small molecule phosphate azaanthracene, its molecular weight is increased, thereby significantly improving the film-forming property on the surface of the conductive substrate, further enhancing the stability and performance of the device.

[0044] In some possible implementations, the general structural formula of the azaanthracene organic polymer is as follows:

[0045] Wherein, X is selected from one of O, S, N, O=S=O, i is an integer between 1 and 40, and n is an integer between 2 and 1000. In this case, the azaanthracene organic polymer has excellent stability, film-forming properties and interaction between macromolecular chains, which can effectively solve the problems of poor small molecule density and easy diffusion of traditional azaanthracene compounds. At the same time, azaanthracene organic polymers do have good solubility, can be dissolved in a variety of single or mixed solvents, and have good solution processing performance. When applied to the hole functional layer of optoelectronic devices, it can improve hole selectivity, reduce interfacial impedance, and improve the stability of optoelectronic devices.

[0046] In some possible implementations, in the general structural formula of the azaanthracene organic polymer, i is an integer between 1 and 20. In this case, the azaanthracene organic polymer has better solubility.

[0047] In some possible implementations, n is an integer between 2 and 800. In this case, the azaanthracene organic polymer has better solubility.

[0048] In some possible implementations, X is selected from O or S.

[0049] In some possible implementations, the general structural formula of the azaanthracene organic polymer is Wherein, n is an integer between 2 and 800. In this case, the azaanthracene organic polymer has good diffusivity, stability, hole selectivity, low interface resistance and solution processability, etc. It can be better applied to the hole functional layer of optoelectronic devices.

[0050] The azaanthracene organic polymers provided in the above embodiments of the present application can be prepared by the following embodiment method.

[0051] In a second aspect, the present invention provides a method for preparing an azaanthracene organic polymer, as shown in the attached Figure 1 As shown, the following steps are included:

[0052] S10. Compound A and diethyl halogenated phosphate as raw materials, and the monomer is prepared by substitution reaction Wherein, X is selected from one of O, S, N, and O=S=O, Y1 and Y2 are independently selected from halogen, and i is an integer between 1 and 40;

[0053] S20. Polymerize the monomer to obtain an intermediate polymer Wherein, n is an integer between 2 and 1000;

[0054] S30. Hydrolyze the intermediate polymer to obtain an azaanthracene organic polymer

[0055] The preparation method of the aza-anthracene organic polymer provided in the embodiment of the present application, after preparing the monomer with compound A and diethyl halogenated phosphate as raw materials, the monomer is subjected to polymerization reaction to obtain an intermediate polymer, and then subjected to hydrolysis reaction, the aza-anthracene organic polymer can be obtained. The synthesis method of the aza-anthracene organic polymer is simple and fast, the reaction conditions are mild, the overall preparation cost is low, and industrial application can be realized, which is suitable for large-scale production and application of industrial industrialization. The obtained aza-anthracene organic polymer also has the advantages of good stability, excellent hole transport performance, good passivation effect, solution processability, good wettability and coating uniformity, and can be better applied to the hole functional layer of the optoelectronic device to obtain an efficient photoelectric conversion efficiency device.

[0056] In some possible implementations, the prepared azaanthracene organic polymer material is applied to the hole transport layer of a perovskite solar cell to improve the photovoltaic performance and stability of the perovskite solar cell. The azaanthracene organic polymer material can be used as a hole transport layer material in an organic solar cell or a perovskite solar cell, or can be used for interface modification on the basis of the original hole transport layer.

[0057] In some possible implementations, the synthesis formula of the azaanthracene organic polymer is as follows:

[0058] In the above step S10:

[0059] In some possible implementations, the structural formula of the monomer is The preparation of the monomer at this time includes the steps of: under an inert atmosphere, 3,7-dibromo-10H-phenoxazine After being dissolved in the first organic solvent with sodium hydride, 2-bromoethyl diethyl phosphate is added for reaction, separated and purified to obtain a monomer. Among them, sodium hydride captures the proton in diethyl [2-(3,7-dibromo-10H-phenoxazine-10-yl) ethyl] phosphonate to generate the corresponding sodium compound, and then undergoes a substitution reaction with 2-bromoethyl diethyl phosphate to obtain the target monomer structure, diethyl [2-(3,7-dibromo-10H-phenoxazine-10-yl) ethyl] phosphonate.

[0060] In some possible implementations, the molar equivalent ratio of diethyl [2-(3,7-dibromo-10H-phenoxazine-10-yl) ethyl] phosphonate, sodium hydride and 2-bromoethyl diethyl phosphate is (0.8-1.2): (3.9-4.1): (2.3-2.7). Under this ratio, it is more conducive to the reaction, reduces the formation of by-products, and improves the purity of the target product monomer. Exemplarily, the molar equivalent ratio of diethyl [2-(3,7-dibromo-10H-phenoxazine-10-yl) ethyl] phosphonate, sodium hydride and 2-bromoethyl diethyl phosphate can be 0.8:3.9:2.3, 1.0:4.0:2.5, 1.2:4.1:2.7 and other typical but non-limiting arbitrary point values ​​or any value between two point values.

[0061] In some possible implementations, the ratio of sodium hydride to the first organic solvent is 1g: (15-25) mL. In this ratio, it is more conducive to the smooth reaction, reducing the generation of by-products and improving the purity of the target product monomer. Exemplarily, the ratio of sodium hydride to the first organic solvent can be 1g: 15mL, 1g: 18mL, 1g: 20mL, 1g: 22mL, 1g: 24mL, 1g: 25mL, etc., typical but non-limiting arbitrary point values ​​or any value between two point values.

[0062] In some possible implementations, the first organic solvent is selected from at least one of N,N-dimethylformamide, dimethyl sulfoxide, and tetrahydrofuran; these organic solvents have good solubility for raw material components such as diethyl [2-(3,7-dibromo-10H-phenoxazine-10-yl)ethyl] phosphonate, sodium hydride, and 2-bromoethyl diethyl phosphate.

[0063] In some possible implementations, the separation and purification steps include: after the reaction is completed, adding ice water, adding an extraction solvent such as ethyl acetate EA for extraction, then adding anhydrous magnesium sulfate for concentration, and then using a silica gel column for elution and purification. Specifically, the silica gel is 200-300 mesh, the column width is 5 cm, the column length is 25 cm, and the gradient is passed through the column petroleum ether PE→PE: dichloromethane DCM=15:1 to obtain a white solid, that is, the target monomer.

[0064] In the above step S20:

[0065] In some possible implementations, the polymerization reaction includes the steps of: dissolving a metal catalyst, bipyridine and 5-cyclooctadiene in a second organic solvent, mixing them under heating conditions, adding monomers for polymerization, and separating to obtain an intermediate polymer. In this case, the metal catalyst, bipyridine and 5-cyclooctadiene act as a catalyst, a ligand and an activated catalyst, respectively, and mixing them under heating conditions can efficiently catalyze the polymerization of monomers to obtain an intermediate polymer.

[0066] In some possible implementations, the metal catalyst includes at least one of Ni(Cod)2, Pd(PPh3)4, and Pd2(dba)3; all of these metal catalysts are capable of catalyzing polymerization reactions.

[0067] In some possible implementations, the temperature condition of the mixing process is 60°C to 90°C, and the mixing time is 0.5 to 1 hour. Under this condition, the reaction between the raw material components is favorable. Exemplarily, the temperature condition of the mixing process can be 60°C, 70°C, 80°C, 90°C, etc., which are typical but non-limiting arbitrary point values ​​or any value between two point values, and the mixing time can be 0.5 hour, 0.8 hour, 1 hour, etc., which are typical but non-limiting arbitrary point values ​​or any value between two point values.

[0068] In some possible implementations, the polymerization reaction temperature is 60°C to 90°C, and the reaction time is 12 to 36 hours; under such reaction conditions, the polymerization reaction between monomers is more favorable to obtain an intermediate monomer polymer. Exemplarily, the polymerization reaction temperature can be 60°C, 70°C, 80°C, 90°C, etc., which are typical but non-limiting values, or any value between two values; the reaction time can be 12 hours, 18 hours, 24 hours, 28 hours, 30 hours, 36 hours, etc., which are typical but non-limiting values, or any value between two values.

[0069] In some possible implementations, the ratio of the metal catalyst to the second organic solvent is 1 g: (10-15) mL; under this ratio, the polymerization reaction is more favorable. Exemplarily, the ratio of the metal catalyst to the second organic solvent can be 1 g: 10 mL, 1 g: 11 mL, 1 g: 12 mL, 1 g: 13 mL, 1 g: 14 mL, 1 g: 15 mL, and other typical but non-limiting arbitrary point values ​​or any value between two point values.

[0070] In some possible implementations, the molar equivalent ratio of bipyridine, 5-cyclooctadiene and monomer is (0.05-0.15): (0.2-0.3): (0.9-1.1). Under this ratio, the reaction is more favorable. Exemplarily, the molar equivalent ratio of bipyridine, 5-cyclooctadiene and monomer can be 0.05:0.2:0.9, 0.1:0.25:1.0, 0.15:0.3:1.1 and other typical but non-limiting arbitrary point values ​​or any value between two point values.

[0071] In some possible implementations, the second organic solvent is selected from at least one of N,N-dimethylformamide, dimethyl sulfoxide, and tetrahydrofuran; these organic solvents have good solubility for raw material components such as metal catalysts, bipyridine and 5-cyclooctadiene, and monomers, which is conducive to the reaction.

[0072] In some possible implementations, after the reaction is completed and cooled to room temperature, dilute hydrochloric acid is slowly added dropwise under stirring until it dissolves into a transparent green solution, and the suspended solid is filtered out. The final product is brown, which is an intermediate polymer.

[0073] In some possible implementations, the intermediate polymer has the structural formula Wherein, n is an integer between 2 and 1000; further, it can be an integer between 2 and 800.

[0074] In the above step S30:

[0075] In some possible implementations, the hydrolysis reaction includes the steps of: dissolving the intermediate polymer and trimethylsilyl bromide in a third organic solvent for a mixed reaction, adding methanol to react and remove excess trimethylsilyl bromide, and separating to obtain an aza-anthracene organic polymer. In this case, the phosphoric acid ester in the intermediate polymer is hydrolyzed by adding trimethylsilyl bromide to obtain a phosphoric acid aza-anthracene polymer.

[0076] In some possible implementations, the ratio of the intermediate polymer to trimethylsilyl bromide is 1g: (8-12) eq; in this case, the hydrolysis reaction is facilitated to obtain a phosphoric acid nitrogen heteroanthracene polymer. Exemplarily, the ratio of the intermediate polymer to trimethylsilyl bromide can be 1g: 8eq, 1g: 9eq, 1g: 10eq, 1g: 11eq, 1g: 12eq, etc., typical but non-limiting arbitrary point values ​​or any value between two point values.

[0077] In some possible implementations, the third organic solvent includes at least one of dichloromethane and 1,4-dioxane. These organic solvents have good solubility for the intermediate polymer and raw material components such as trimethylsilyl bromide, which is conducive to the reaction.

[0078] In some possible implementations, the intermediate polymer and trimethylsilyl bromide are dissolved in a third organic solvent for a mixed reaction, methanol is added to remove excess trimethylsilyl bromide, the solution is concentrated by vacuum distillation, precipitated in diethyl ether, and filtered and rinsed with diethyl ether to obtain the final product, anthracene organic polymer.

[0079] In some possible implementations, the intermediate polymer has the structural formula The structural formula of azaanthracene organic polymers is Here, n is an integer between 2 and 1000.

[0080] In a third aspect, an embodiment of the present application provides a photoelectric device, comprising a substrate, a photoelectric functional layer, an electron transport layer, a hole transport layer and an electrode; wherein the hole transport layer contains the azaanthracene organic polymer as described above, or the azaanthracene organic polymer prepared by the above method.

[0081] The optoelectronic device provided by the embodiment of the present application, the hole transport layer contains the above-mentioned aza-anthracene organic polymer, the aza-anthracene organic polymer not only has a large coverage factor and good interface compatibility for conductive substrates such as ITO and FTO, but also has good film-forming performance on the surface of the conductive substrate; and the phosphate group of the aza-anthracene organic polymer can form a chemical bond with the conductive oxide on the surface of the conductive glass, enhance the binding ability with the transparent conductive oxide, shorten the interface spacing, reduce the interface impedance, thereby enhancing the adsorption and transmission ability of holes, and enhancing the stability and other properties of the device. In addition, the aza-anthracene organic polymer has good conductivity, which makes it insensitive to the coating thickness and the roughness of the conductive glass surface, thus showing better hole selectivity and hole transport performance. Moreover, the aza-anthracene organic polymer can better infiltrate the perovskite precursor solution, which is conducive to the large-scale preparation of the perovskite active layer, and passivate the perovskite layer, inhibit the charge recombination at the interface between the perovskite active layer and the hole transport layer, improve the device hole selectivity, reduce the interface impedance, and improve the device stability and photoelectric conversion efficiency. It has both important scientific significance and extremely high industrial value.

[0082] In some possible implementations, the nitrogen-anthracene organic polymer material is dissolved in a single or mixed solvent such as toluene, chlorobenzene, chloroform, dichloromethane, methanol, ethanol, isopropanol, etc., and processed into a thin film by spin coating, scraper coating, slit coating, dip coating, spraying, etc. to prepare an optoelectronic device based on the nitrogen-anthracene organic polymer material.

[0083] The application forms of the azaanthracene organic polymer in the hole transport layer of the embodiment of the present application are diverse. In some possible implementations, the azaanthracene organic polymer modifies the interface of the hole transport layer. In some possible implementations, the azaanthracene organic polymer is doped into the hole transport layer. In some possible implementations, the self-assembled monolayer based on the azaanthracene organic polymer is used as a hole transport layer.

[0084] Self-assembled monolayers (SAMs) are being widely used as hole-selective layers in high-performance inverse perovskite solar cell devices. Currently commonly used SAMs usually use alkyl groups to connect aromatic amine groups and anchoring groups that can transmit holes. Due to the localization of electrons / charges, SAMs with non-conjugated structures usually have poor stability, which in turn affects the stability of battery devices. The self-assembled monolayers (SAMs) based on azaanthracene organic polymers in the embodiments of the present application not only significantly improve the hole selectivity, but also reduce the interface impedance, effectively inhibit non-radiative recombination, and thus improve the stability of the device.

[0085] In some possible implementations, the optoelectronic device includes at least one of a solar cell, a field effect transistor, a photodetector, a ray detector, and a light-emitting diode. The nitrogen-anthracene organic polymer of the embodiment of the present application can be used as an anode buffer material in an organic or perovskite solar cell device. The nitrogen-anthracene organic polymer provided in the embodiment of the present application has a simple synthesis step and a low overall preparation cost, and can be industrialized and applied with advantages such as good stability, excellent hole transport performance, good passivation effect, solution processability, good wettability and coating uniformity, and high photoelectric conversion efficiency.

[0086] In some possible implementations, the solar cell includes at least one of a perovskite solar cell and an organic solar cell. The perovskite solar cell in the embodiment of the present application has a photoelectric conversion efficiency of 1% to 30%, and the organic solar cell has a photoelectric conversion efficiency of 1% to 20%.

[0087] In some embodiments, the above-mentioned nitrogen-anthracene organic polymer material is applied to the hole transport layer of the perovskite solar cell to improve the photovoltaic performance and stability of the perovskite solar cell. The nitrogen-anthracene organic polymer material can be used as a hole transport layer material in an organic solar cell or a perovskite solar cell, or can be used for interface modification on the basis of the original hole transport layer.

[0088] In some possible implementations, the device structure of the solar cell includes a positive structure and a negative structure; wherein the structure of the solar cell with the positive structure includes, from bottom to top, a conductive substrate, an electron transport layer, a perovskite / organic light absorption layer, a hole transport layer (including the above-mentioned nitrogen-anthracene organic polymer) and a metal counter electrode, such as the attached Figure 2 As shown. In the positive structure, light is incident from one side of the transparent conductive substrate, first enters the electron transport layer, and then reaches the light absorbing layer. After the light is absorbed by the light absorbing layer, electron-hole pairs are generated. The electrons are collected by the electron transport layer and transmitted to the transparent conductive substrate, while the holes pass through the hole transport layer to the metal electrode, thereby forming a photocurrent. The structural components of the inverted solar cell include, from bottom to top: a conductive substrate, a hole transport layer (including the above-mentioned nitrogen-anthracene organic polymer), a perovskite / organic light absorbing layer, an electron transport layer, and a metal counter electrode, as shown in the attached figure. Figure 3 As shown. In the inversion structure, light is also incident from the side of the transparent conductive substrate, but is first received by the hole transport layer and then reaches the light absorbing layer. The electron-hole pairs generated in the absorption layer are neutralized, and the electrons pass through the electron transport layer to the metal electrode, thus forming a photocurrent. This structure may have a higher photoelectric conversion efficiency in some cases, because the hole transport layer can better match the transparent conductive substrate and reduce the charge recombination loss at the interface.

[0089] In some possible implementations, the perovskite light-absorbing layer includes a metal halide perovskite, whose chemical formula is ABX2, wherein A includes but is not limited to methylamine ion, formamidine ion, cesium, rubidium, potassium, sodium, ammonium ion, ethylamine, propylamine, butylamine, aniline, benzylamine, phenylethylamine, or a combination of the above components; B includes lead, tin, cadmium, germanium, zinc, nickel, or a combination of the above components. X is fluorine, chlorine, bromine, iodine anion or a combination of the above components.

[0090] In some possible implementations, the hole transport layer includes PTAA (poly [bis (4-phenyl) (2,4,6-trimethylphenyl) amine]), Spiro-OMeTAD (2,2',7,7'-tetrakis [N,N-di (4-methoxyphenyl) amino] -9,9'-spirobifluorene), PEDOT:PSS (poly (3,4-ethylenedioxythiophene): polystyrene sulfonate), NiO, MoO3, V2O5, Poly-TPD (poly [bis (4-phenyl) (4-butylphenyl) amine]), EH44, P3HT (poly (3-hexylthiophene)) or a combination of the above materials.

[0091] In some possible implementations, the electron transport layer includes C6O, BCP, TiO2, SnO2, PCBM (fullerene derivatives, commonly [6,6]-phenyl-C61-butyric acid methyl ester (

[60] PCBM) and [6,6]-phenyl-C71-butyric acid methyl ester (

[70] PCBM)), ICBA, ZnO, ZrAcac (zirconium acetylacetonate (or zirconium acetylacetonate complex)), LiF, TPBi (1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene), PFN, Nb2O5 or a combination of the above materials.

[0092] In some possible implementations, the electrodes of the solar cell contain one or more of gold, silver, copper, aluminum, carbon, and chromium.

[0093] In order to enable the above implementation details and operations of the present application to be clearly understood by those skilled in the art, as well as to demonstrate the significant improvement in the performance of the azaanthracene organic polymers and their preparation methods and applications in the embodiments of the present application, the above technical solutions are illustrated by multiple embodiments below.

[0094] Example 1

[0095] A polyphenoxazine polymer, the preparation of which comprises the following steps:

[0096] 1. Add 3,7-dibromo-10H-phenoxazine (1±0.2eq), 60% sodium hydride (4±0.1eq), replace nitrogen three times, inject DMF (1g sodium hydride: 20mL DMF), add diethyl(2-bromoethyl)phosphonate dropwise, (2.5±0.2eq), react for 2h, add 500mL of ice water, extract three times with 500mL*3 ethyl acetate EA, concentrate after anhydrous magnesium sulfate, silica gel 200-300 mesh, column width 5cm, column length 25cm, gradient column petroleum ether PE→PE: dichloromethane DCM=15:1,

[0097] A white solid, i.e., the monomer, is obtained. Diethyl[2-(3,7-dibromo-10H-phenoxazin-10-yl)ethyl]phosphonate.

[0098] 2. Dissolve Ni(Cod)2 (5% eq), bipyridine (0.1±0.05 eq), and 1,5-cyclooctadiene (0.25±0.05 eq) in DMF (1 g Ni(Cod)2:12.5 mL DMF), heat and stir at 80°C for half an hour, dissolve diethyl [2-(3,7-dibromo-10H-phenoxazine-10-yl)ethyl]phosphonate (1±0.1 eq) in DMF (1 g Ni(Cod)2:12.5 mL DMF), slowly add dropwise to the reaction system, and continue stirring at 80°C for 24 hours. After the reaction is completed, cool to room temperature, slowly add dilute hydrochloric acid under stirring until it dissolves into a transparent green solution, filter out the suspended solid, and the final product is brown, that is, the intermediate polymer, named polydiethyl [2- (3,7-dibromo-10H-phenoxazin-10-yl) ethyl] phosphonate, diethyl (2- (10H-phenoxazin-10-yl) ethyl) phosphonate-homopolymer,

[0099] 3. Add trimethylsilane bromide (10±2eq) to 1g of polydiethyl [2-(3,7-dibromo-10H-phenoxazine-10-yl)ethyl]phosphonate and 100mL of dichloromethane, and stir at room temperature for 24 hours. After the reaction is completed, add excess methanol to the reaction system to remove excess trimethylsilane bromide. Concentrate the solution by vacuum distillation, precipitate in ether, and filter and rinse with ether to obtain the final product, a polyphenoxazine polymer, named (2-(10H-phenoxazin-10-yl)ethyl)phosphonic acid-homopolymer,

[0100] Example 2

[0101] A perovskite solar cell, the preparation of which comprises the following steps:

[0102] 1. Cut fluorine-doped tin oxide transparent conductive glass (FTO conductive glass) into squares with a side length of 1.5 cm, and use a photolithography machine to etch according to the electrode requirements to obtain a substrate.

[0103] 2. Prepare 6 mL of 75% di(acetylacetonate)titanate diisopropyl solution, 4 mL of acetylacetone, and 90 mL of anhydrous ethanol, stir the mixed solution overnight, and use it as the dense layer solution.

[0104] 3. Mix titanium dioxide slurry and anhydrous ethanol in a mass ratio of 1:6 and stir overnight to obtain a mesoporous layer solution.

[0105] 4. Dissolve 1.1 mol of PbI2, 1.0 mol of formamidine hydroiodide FAI, 0.2 mol of PbBr2, and 0.2 mol of methylamine bromide MABr in dimethyl sulfoxide DMSO / dimethylformamide DMF (volume ratio of 1:4) and stir overnight to obtain (FAPbI3) 0.85 (MAPbBr3) 0.15 Perovskite precursor solution.

[0106] 5. Dissolve 80 mg of Spiro-OMeTAD in 875.1 mL of chlorobenzene, add 31.6 μL of tert-butylpyridine (TBP), 18.1 μL of acetonitrile solution of lithium bis(trifluoromethylsulfonylimide) (Li-TFSI) (500 mg·mL-1) and 7.83 μL of acetonitrile solution of tri[4-tert-butyl-2-(1H-pyrazol-1-yl)pyridine]cobalt (FK209) (300 mg·mL-1) in sequence, and stir for four hours to obtain a Spiro-OMeTAD solution.

[0107] 6. Weigh 30 mg of the polyphenoxazine polymer prepared in Example 1 and dissolve it in 60 mL of chlorobenzene. Then add 19.75 μL of tributyl phosphate TBP, 11.32 μL of acetonitrile solution of lithium bis(trifluoromethanesulfonyl)imide Li-TFSI (500 mg / mL) and 4.90 μL of acetonitrile solution of FK209 (300 mg / mL) and stir for four hours to obtain a polyphenoxazine polymer solution with a concentration of 0.5 mg / mL.

[0108] 7. Use tap water containing detergent, deionized water, acetone, and ethanol to ultrasonically clean the FTO conductive glass for 20 minutes, and place it in an 80°C air drying oven for drying. Use an ear cleaning bulb to blow clean the FTO conductive surface, and then treat it with ozone for 30 minutes.

[0109] 8. All prepared solutions except the mesoporous layer solution were filtered with a needle filter (polytetrafluoroethylene filter membrane, pore size 0.22 μm) before use.

[0110] 9. Use a spray gun to evenly spray the dense layer solution prepared in step 2 above onto the FTO conductive glass substrate preheated at 450° C., heat at 450° C. for 30 minutes and then cool naturally to obtain a dense titanium dioxide layer.

[0111] 10. The mesoporous layer solution prepared in step 3 was evenly spin-coated on the sintered titanium dioxide dense layer using a spin coater at a speed of 5000 for 30 seconds, first heated at 100°C for 10 minutes, and then sintered at 500°C for 1 hour to obtain a mesoporous titanium dioxide layer. Together with the dense titanium dioxide layer, it constitutes an electron transport layer.

[0112] 11. Take 25 μL of perovskite precursor solution and spread it evenly on the sintered mesoporous titanium dioxide layer. Spin-coat the perovskite precursor solution evenly on the mesoporous titanium dioxide layer using a two-step method of 1000 rpm for 10 seconds and 5000 rpm for 30 seconds. Quickly add 120 μL of chlorobenzene as an anti-solvent in the last 10 seconds of the second step. Anneal the spin-coated film at 100 °C for 1 hour to obtain a perovskite film.

[0113] 12. Take 25 μL of the prepared polyphenoxazine polymer solution with a concentration of 0.5 mg / mL and Spiro-OMeTAD solution and spin-coat them onto the sintered perovskite film at a speed of 5000 and a process parameter of 30 seconds to obtain a hole transport layer.

[0114] 13. A gold electrode with a thickness of about 80 nm was deposited on the above-mentioned film with the hole transport layer spun on it using a vacuum coating machine to produce a perovskite solar cell. The cell test area was 0.0625 cm 2 , the structure of perovskite solar cell is shown in the attached figure Figure 4 shown.

[0115] Example 3

[0116] A perovskite solar cell, which differs from Example 1 in that: in step 6, 40 mg of the polyphenoxazine polymer prepared in Example 1 is weighed and dissolved in 40 mL of chlorobenzene, and 19.75 μL of tributyl phosphate TBP, 11.32 μL of acetonitrile solution of lithium bis(trifluoromethanesulfonyl)imide Li-TFSI (500 mg / mL) and 4.90 μL of acetonitrile solution of FK209 (300 mg / mL-1) are added in sequence and stirred for four hours to obtain a polyphenoxazine polymer solution with a concentration of 1 mg / mL.

[0117] Example 4

[0118] A perovskite solar cell, which differs from Example 1 in that: in step 6, 50 mg of the polyphenoxazine polymer prepared in Example 1 is weighed and dissolved in 25 mL of chlorobenzene, and 19.75 μL of tributyl phosphate TBP, 11.32 μL of acetonitrile solution of lithium bis(trifluoromethanesulfonyl)imide Li-TFSI (500 mg / mL) and 4.90 μL of acetonitrile solution of FK209 (300 mg / mL-1) are added in sequence and stirred for four hours to obtain a polyphenoxazine polymer solution with a concentration of 2 mg / mL.

[0119] Comparative Example 1

[0120] A perovskite solar cell, which differs from Example 1 in that: the polyphenoxazine polymer solution in step 6 is not prepared; the polyphenoxazine polymer solution is not added in step 12, and the prepared hole transport layer does not contain the polyphenoxazine polymer.

[0121] In order to verify the progress of the embodiments of the present application, the perovskite solar cells prepared in the above embodiments 2 to 4 and comparative example 1 were respectively subjected to the following open circuit voltage, short circuit current density, fill factor, and photoelectric conversion efficiency performance tests. The test results are shown in Table 1 and the attached Figures 5 to 8 As shown, Figure 5 The voltage-current density test diagram of the perovskite solar cell provided in Example 2; Figure 6 The voltage-current density test diagram of the perovskite solar cell provided in Example 3; Figure 7 The voltage-current density test diagram of the perovskite solar cell provided in Example 4; Figure 8 The voltage-current density test diagram of the perovskite solar cell provided for comparative example 1.

[0122] Table 1

[0123]

[0124] According to the above Table 1 and the attached Figures 5 to 8 The test results show that compared with the perovskite solar cell without the addition of the polyphenoxazine polymer of Example 1 of the present application, the polyphenoxazine polymer synthesized in Example 1 is added to the hole transport layer of the perovskite solar cell device of Examples 2 to 4 of the present application, so the devices all show excellent photoelectric performance such as photoelectric conversion efficiency. This is mainly attributed to the excellent film-forming properties and interactions between macromolecular chains of polyphenoxazine polymers, which improve the stability of perovskite solar cell devices. In addition, polyphenoxazine polymers have good conductivity, coverage factor and interface compatibility, making them insensitive to coating thickness and surface roughness of conductive glass, further improving the stability of the device, reducing interface impedance, and improving hole selectivity. In addition, the phosphate group of polyphenoxazine polymers can form chemical bonds with conductive glass, which not only enhances the binding ability with TCO, but also helps to passivate the perovskite layer and inhibit charge recombination at the interface of perovskite active layer / hole transport layer. This strong binding ability improves the stability and efficiency of hole transport.

[0125] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. An azaanthracene organic polymer, characterized in that: The general structural formula of the azaanthracene organic polymer is as follows: Wherein, X is selected from one of O, S, N, and O=S=O, i is an integer between 1 and 40, and n is an integer between 2 and 1000.

2. The azaanthracene organic polymer according to claim 1, characterized in that The general structural formula of the azaanthracene organic polymer is as follows:

3. The azaanthracene organic polymer according to claim 2, characterized in that: In the general structural formula of the azaanthracene organic polymer, i is an integer between 1 and 20; and / or, n is an integer between 2 and 800; And / or, X is selected from O or S.

4. The azaanthracene organic polymer according to claim 3, characterized in that: The general structural formula of the azaanthracene organic polymer is: Here, n is an integer between 2 and 800.

5. A method for preparing an azaanthracene organic polymer, characterized in that: The following steps are involved: Compound A and diethyl halogenated phosphate as raw materials, and the monomer is prepared by substitution reaction Wherein, X is selected from one of O, S, N, and O=S=O, Y1 and Y2 are independently selected from halogen, and i is an integer between 1 and 40; The monomer is polymerized to obtain an intermediate polymer Wherein, n is an integer between 2 and 1000; The intermediate polymer is subjected to a hydrolysis reaction to obtain an azaanthracene organic polymer.

6. The method for preparing an azaanthracene organic polymer according to claim 5, characterized in that: The structural formula of the monomer is The preparation of the monomer comprises the following steps: dissolving 3,7-dibromo-10H-phenoxazine and sodium hydride in a first organic solvent under an inert atmosphere, adding 2-bromoethyl diethyl phosphate to react, and separating and purifying to obtain the monomer; And / or, the polymerization reaction comprises the steps of: dissolving the metal catalyst, bipyridine and 5-cyclooctadiene in a second organic solvent, mixing them under heating conditions, adding the monomer to carry out polymerization reaction, and separating to obtain the intermediate polymer; And / or, the hydrolysis reaction comprises the steps of: dissolving the intermediate polymer and trimethylsilyl bromide in a third organic solvent for a mixed reaction, adding methanol to react and remove excess trimethylsilyl bromide, and separating to obtain the azaanthracene organic polymer.

7. The method for preparing an azaanthracene organic polymer according to claim 6, characterized in that: The molar equivalent ratio of the diethyl [2-(3,7-dibromo-10H-phenoxazine-10-yl) ethyl] phosphonate, the sodium hydride and the 2-bromoethyl diethyl phosphate is (0.8-1.2): (3.9-4.1): (2.3-2.7); And / or, the ratio of the sodium hydride to the first organic solvent is 1 g: (15-25) mL; And / or, the metal catalyst comprises at least one of Ni(Cod)2, Pd(PPh3)4, Pd2(dba)3; And / or, the temperature condition of the mixing treatment is 60° C. to 90° C., and the mixing time is 0.5 to 1 hour; And / or, the polymerization reaction temperature is 60°C to 90°C, and the reaction time is 12 to 36 hours; and / or, the ratio of the metal catalyst to the second organic solvent is 1 g: (10-15) mL; and / or, the molar equivalent ratio of the bipyridine, the 5-cyclooctadiene and the monomer is (0.05-0.15):(0.2-0.3):(0.9-1.1); And / or, the first organic solvent and the second organic solvent are independently selected from at least one of N,N-dimethylformamide, dimethyl sulfoxide and tetrahydrofuran; and / or, the ratio of the intermediate polymer to the trimethylsilyl bromide is 1 g: (8-12) eq; And / or, the third organic solvent includes at least one of dichloromethane and 1,4-dioxane.

8. The method for preparing an azaanthracene organic polymer according to any one of claims 5 to 7, characterized in that: The structural formula of the intermediate polymer is The structural formula of the azaanthracene organic polymer is 9. A photoelectric device, characterized in that: It comprises a substrate, a photoelectric functional layer, an electron transport layer, a hole transport layer and an electrode; wherein the hole transport layer contains the azaanthracene organic polymer as described in any one of claims 1 to 4, or the azaanthracene organic polymer prepared by the method as described in any one of claims 5 to 8.

10. The optoelectronic device according to claim 9, characterized in that The optoelectronic device includes at least one of a solar cell, a field effect transistor, a photodetector, a radiation detector, and a light emitting diode; and / or, the azaanthracene organic polymer modifies the interface of the hole transport layer; And / or, a self-assembled monolayer based on the azaanthracene organic polymer is used as the hole transport layer; And / or, the azaanthracene organic polymer is doped into the hole transport layer.